(untitled) (Research, Society and Development, 2021)
Objective: to assess the clinical severity of the patient admitted to the ICU using the Modified Early Warning Score. Method: cross-sectional, analytical study with a quantitative approach; was performed in the ICU of a regional reference hospital. Data were collected from patients’ medical records using an instrument focusing on: reason for admission to the ICU; underlying disease and comorbidities; clinical complications and interventions performed in the ICU; the sample consisted of 265 medical records considering a 5% significance level and a relative sampling error of 8%. Results: the age groups of 41-50 (13%) and 71-80 years (18%) prevailed; as to the reason for admission, it was identified: traumatic injuries (30%), pneumonia (12%), stroke (11%) and hemorrhagic stroke (10%). The severity assessment using the MEWS identified: values between 1 and 12 with a mean of 5.2; highest mortality rate associated with MEWS classified between 4 to 6. Among patients who used IMV, for 40.3% the MEWS was between 4-6. The longest stay in the ICU was recorded in patients with MEWS from 1-4. Conclusion: the higher scores in the MEWS are associated with greater clinical severity, as well as greater need for care, allowing the establishment of priorities in care.